Hospital Care and Surgical Treatment of Children With Congenital Upper Limb Defects. (September 2020) - Koskimies-Virta, E.; Helenius, I.; Pakkasjärvi, N.; Nietosvaara, Y.
Background and Aims: To evaluate hospital care of children with congenital upper limb defects. Materials and Methods: Three hundred and sixty-two children with an upper limb defect, born 1993–2005, and alive after birth admission were identified in the Finnish Register of Congenital Malformations. The data on hospital care, with focus on operative treatment, were collected from the National Hospital Discharge Register, until 31 December 2009. Mean follow-up was 10.2 years (range: 4–17 years). The results were compared with data on the whole children population (1.1 million) in Finland. Results: Most children (321, 87%) with upper limb defects had hospital admissions: on average, one admission/year (range: 0–36), and they were treated in hospital 5 days/year (range: 0–150), which is 11-fold compared with an average child in Finland. Four surgical procedures/child were done (range: 0–45), including one hand surgical procedure. The most common procedures were orthopedic (513); gastrointestinal (263); ear, nose, and throat (143); dental (118); thoracic (48); and urologic (44). Of the 513 orthopedic procedures, 326 were directed to upper limbs, 107 to the lower limbs, and 10 to the spine. Median operation age was 2 years 7 months. Altogether, 60% of hospital admissions were non-surgical. Leading causes of non-operative hospital admissions were congenital anomalies (32%), gastroenterological problems (20%), respiratory tract conditions (13%), neurological problems (7%), perinatal conditions (5%), and infectious diseases (5%). Conclusion: Treatment of children with upper limb defects is teamwork between pediatric and surgical subspecialties. Burden of hospital care is 11-fold as compared with an average child.